Sports Science Research and Technology Support: Second International Congress, icSPORTS 2014, Rome, Italy, October 24-26, 2014, Revised Selected Papers (Communications in Computer and Information Science, 556, 2015)
The present book includes extended and revised versions of a set of selected papers from the Second International Congress on Sport Sciences Research and Technology Support (icSPORTS 2014), held in Rome, Italy, during October 24-26, 2014. The purpose of the International Congress on Sport Sciences Research and Technology Support is to bring together researchers and practitioners in order to exchange ideas and developed synergies highlighting the benefits of any kind of technology for sports, either in general or regarding a particular case of application. icSPORTS 2014 was sponsored by the Institute for Systems and Technologies of Information, Control and Communieation (INSTICC) and had the institutional sponsorship of Universidade de Lisboa (Faculdade de Motricidade Humana), the Olympic Committee of Portugal, and the Norwegian School of Sport Scienees. It was held in cooperation with the European College of Sport Science (ECSS); European College of Sports and Exercise Physicians (ECOSEP); International Association of Computer Science in Sport (IACSS); Societa Italiana delle Seienze Motorie e Sportive; European Federation of Sport Psychology; Societa Italiana di Anatomia; IASK -International Association of Sport Kinetics; European Association for Sport Management. icSPORTS 2014 also had as R&D group partners the following projects: BLINDTRACK (guiding system for visually impaired for individual running on the track) and REPOPA (research into policy to enhance physical activity). The congress received 131 paper submissions from 37 countries in all continents. To evaluate each submission, a double-blind paper review was performed by the Program Committee. After a stringent selection process, 14 papers were published and presented as fuIl papers, i.e., completed work (30' oral presentation), leading to a "full-paper" acceptance ratio of about 11.5 %, which shows the intention of preserving a high-quality forum for the next editions of this congress. icSPORTS's program included panels and four invited talks delivered by internationally distinguished speakers, namely: Luis Paulo Reis (University of Minho, Portugal), Peter Federolf (Norwegian University for Science and Technology, Norway), Antoine Nordez (University of Nantes, France), and Hermano Igo Krebs (Massachusetts Institute of Technology, USA).